"Tacierzyństwo", "surogatka", "bachor" - "brzydkie słowa" związane z rodziną w ocenie językoznawców i użytkowników języka = "Paternity", "surrogate", "brat" - "bad words" connected with family in linguists and language users assessment - Idzikowska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article I draw attention to aesthetic aspect of denotations concerned with family, which function in media space. I refer to pledged feelings and opinions expressed by the users of the language and linguists.
Keywords: słownictwo; rodzina; media; estetyka językowa; vocabulary; family; media message; linguistic aesthetics